Grammatical Means of Expressing the Semantics of Imperative in the Speech Genre “Command” - A. E. Osipchuk (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the study of ways of expressing imperative in the speech genre “command” based on the material of artworks by B. L. Vasiliev and V. N. Voinovich. Particular attention is paid to imperative intention as the leading genre-forming feature of the studied speech genre. The most regular verbal, adverbial (particles, unions) and non-verbal (particles, interjections, nouns and adverbs) means of expressing the semantics of imperativeness are described. Grammatical means expressing the semantics of imperative in the speech genre “command” are divided into four groups: constructions that include the verb imperative; constructions that include other forms of the verb; constructions represented by the unity of verb and non-verb forms; non-verbal means of expressing imperative. The article notes that the most frequent verbal means of expressing imperativeness are verbs in the form of imperative, infinitive and prohibitive. The expressiveness of statements, the imperative semantics of which is expressed by forms of verbs of indicative mood and non-verb morphological means, is emphasized. The main intention of the command in such contexts is supplemented by various shades of motivation: a request, a wish, a demand, a call, an indication of how the action was performed, and others. The analysis and comparison of the means of expressing imperative in the texts of the works of B. L. Vasiliev and V. N. Voinovich is carried out.